PERMAINAN TRADISIONAL JAWA SEBAGAI STRATEGI PEMBELAJARAN BERBASIS KEARIFAN LOKAL UNTUK MENUMBUHKAN KETERAMPILAN GLOBAL DI MI/SD - Prastowo, Andi (PD PGMI se Indonesia, 2018)
The study of games in education is not new, from traditional games to modern website-based games have been done. Studies have even proved that traditional games have more proven value and benefits in the long run for education than modern games. However, the fact that the quality of education in various countries of the world is uneven, although they also know and have traditional games as part of its cultural elements. Like one of them can be seen in the quality of basic education in Indonesia, especially in the ability of thinking high level is still low. Moreover, in the 21st century students are required to have global skills of the 21st century. From this point the need to be studied about how the traditional Javanese games, as one of the greatest cultural heritages in Indonesia, can serve as a strategy to cultivate 21st century global skills for madrasah ibtidaiyah / primary school. This research is done by literature study with the method of textual criticism and external critic and then continued with synthesis. The findings of this study indicate that some traditional Javanese games are basically potential as a strategy to cultivate 21st century skills. This is not apart because the characteristics and form of some traditional Javanese game contains characteristics of 21st century skills that include critical thinking, communication, cooperation, and creativity.